But I don't eat ants - Marvin, Dan (Daniel W.) (New York : Pow!, 2017)
This clever take on the picky-eater is full of wry humor and silly puns as the anteater takes us through the food he LOVES to eat, all while repeating the refrain, but I don t eat ants. That is until dinnertime when his mom presents him with a fiery surprise.
Keywords: Food -- Juvenile fiction; Food habits -- Juvenile fiction; Myrmecophagidae -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Anteaters -- Juvenile fiction